Gambling Revenues as a Public Administration Issue: Electronic Gaming Machines in Victoria - Pickernell, D.; Keast, R.; Brown, Kerry; Yousefpour, N.; Miller, C. (Springer New York LLC, 2013)
Gambling activities and the revenues derived have been seen as a way to increase economic development in deprived areas. There are also, however, concerns about the effects of gambling in general and electronic gaming machines (EGMs) in particular, on the resources available to the localities in which they are situated. This paper focuses on the factors that determine the extent and spending of community benefit-related EGM-generated resources within Victoria, Australia, focusing in particular on the relationships between EGM activity and socio-economic and social capital indicators, and how this relates to the community benefit resources generated by gaming.